New year as a moment of change in pro-environmental product consumption: evaluating the habit discontinuity and self-activation hypotheses using a large UK retail dataset - Haggar, Paul; Sachdev, Yasmin; Whitmarsh, Lorraine; Goulding, James; Smith, Andrew; Smith, Gavin (Frontiers in Psychology, 2025)
IntroductionThe New Year, and the New Year’s Resolution tradition, may establish January as a moment of personal change: when there could be a temporal landmark for making a “fresh start,” a habit discontinuity, and value activation. As such, January may afford opportunities for personal pro-environmental lifestyle changes, such as by changing product choices.MethodTo investigate this empirically, we analyzed existing data from a 2016 survey of retail customers (N = 12,968) linked to 35 months of their sales data (2012–2015) provided by a leading healthcare retailer in the United Kingdom. We compared sales in January to those in other months, focusing on sales of green product varieties and overall product sales (as a dematerialization indicator), and sales of two self-enhancing health product types (nicotine replacement therapy products and weight reduction products) for comparison.ResultsOur results confirmed that sales of self-enhancing health products were greater in January than in other months, but we found limited evidence for pro-environmental consumption in January, and no evidence to support the habit discontinuity or value activation hypotheses.DiscussionWe discuss these results with respect to behavior change intervention potential and moments of change theory.